Quasifission and fusion-fission processes in the reactions Kr78+Ca40 and Kr86+Ca48 at 10 MeV/nucleon bombarding energy - Kalandarov Sh. A. Shukhrat Atazhanovich; Lacroix D.; Adamyan G. G. Gurgen Grigorjevich; Antonenko N. V. Nikolay Viktorovich; Wieleczko J. P.; Pirrone S.; Politi G. (2016, 2016)
Title screen